Energy poverty measures and the identification of the energy poor: A comparison between the utilitarian and multidimensional approaches in Chile - Carlos Villalobos Barría; Carlos Chávez Rebolledo; Adolfo Uribe (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2019)
This work explores the consequences that different energy poverty definitions might have in the energy policy debate. We estimate the ten percent rule index (TPRI) while proposing and measuring a multidimensional energy poverty index (PMEPI). Both indices uses the 2017 National Survey of Public Perception on Energy applied to a sample of 3,500 households in Chile. Although both measures find that the energy poor represents about 15% of the population, energy poverty levels vary differently across the population depending on the employed measure. Moreover, the indices produce different energy poverty rankings across the territory, and most energy poor households are either TPRI poor or PMEPI poor. We found that this discrepancy between both energy poverty measures is mostly explained by territorylinked factors such as public lighting, service quality, service reliability, and thermal comfort. Consequently, an energy poverty analysis based solely on income or energy expenditure information (TPRI) is likely to neglect supply side constraints that are captured by the PMEPI. When identifying and targeting the energy deprived, the conclusion is that both energy poverty measures should not be used as substitutes but as complements.
Keywords: 330; Energy Poverty; Poverty; Multidimensional Energy Poverty Index; Ten Percent Rules Energy Poverty Index; Affordability; Reliability of Energy Services; Quality of Energy Services